Neuroanatomi DID: Hipokampus, Amigdala, dan Trauma Masa Kanak-kanak - Angeline Rosemarie Yohana Hutahaean (Aesculapius Medical Journal, 2026)
Abstract [Neuroanatomy of DID: Hippocampus, Amygdala, and Childhood Trauma] Dissociative Identity Disorder (DID) is a complex dissociative disorder characterized by identity fragmentation, amnesia, and emotional dysregulation. Repeated childhood trauma has been shown to be a major factor in the etiology of DID, leaving persistent changes in the hippocampus and amygdala, which play a crucial role in memory and emotional regulation. The review revealed reduced hippocampal volume in DID patients, particularly in the CA2–3 subfield, CA4–dentate gyrus, and subiculum, which is associated with impaired memory consolidation and dissociative amnesia. Conversely, the amygdala exhibits hyperactivity to emotional stimuli, triggering hypervigilance and emotional dysregulation. Neuroimaging studies, including fMRI perfusion and PET, consistently support the existence of two primary identities: the Apparently Normal Part (ANP) and the Emotional Part (EP), with distinct brain activation patterns that cannot be replicated in healthy individuals. These findings strengthen the neurobiological validity of DID. Thus, childhood trauma plays a central role in the development of DID through dissociative mechanisms and neuroanatomical changes in the hippocampus and amygdala, opening up opportunities for the development of biomarkers for more accurate diagnosis and trauma-based therapeutic interventions. Keyword: Dissociative Identity Disorder, childhood trauma, hippocampus, amygdala, neuroimaging.